PEMBERDAYAAN ANAK SDN 2 BATUAN KALER SUKAWATI GIANYAR DALAM OPTIMALISASI UNIT KESEHATAN SEKOLAH MELALUI PELATIHAN DOKTER KECIL - Ni Made Diah Pusparini Pendet; Ni Putu Eka Febianingsih; Desak Made Puja Astuti; I Kadek Agus Dwija Putra (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
The School Health Unit or Unit Kesehatan Sekolah (UKS) aims toimproved healthy live habits and the health status of students. The goal of UKS canbe achieved if it has cadres with good knowledge, abilities and skills to implementedand transmitted healthy live behaviors to their environment. The UKS cadre is calleda Little Doctor. The purpose of this activity was to increase student participation inthe UKS program at SDN 2 Batuan Kaler Sukawati. Method: This activity wascarried out at SDN 2 Batuan Kaler Sukawati, with the Community Empoweringapproach. A total of 10 selected students were trained for 3 days (January 24th - 26th2014). The training done by lectures, discussions and demonstrations. Results: Basedon the evaluation in the form of pretest and posttest, it was found that there was anincrease in the knowledge of the students / Little Doctors, from 50% to 80%. Thetraining also provided enrichment about UKS for teachers in SDN 2 Batuan Kaler.Conclusion: UKS cadres were formed, namely Little Doctors in SDN 2 Batuan Kalerwith 10 students, with a good level of knowledge (80%) after 3 days of training. It isexpected that the established Little Doctors can become health cadres for peers, theschool environment and home environment to apply the healthy live.